Pecha Kucha: The Use of Visual Storytelling to Improve Students Presentation Skills in Marketing Course (S/O: 14765) - Abdul Hamid, Mohd Noor (UUM, 2021)
This study examines the effects of the Pecha Kucha method as opposed to traditional modes of presentation on marketing students’ competency in giving a presentation. Data for the study is collected from students’ self-evaluation and lecturers’ evaluation of the presentations. Results from students’ self-evaluation showed that modes of presentation did not contribute significantly on students’ overall performance. However, those who adopted Pecha Kucha did show significant improvements in their ability to use physical behaviour or gestures. On the contrary, results from the lecturers’ evaluation showed that Pecha Kucha method did have significant effects in improving students’ overall performance as well as in each components evaluated. For these reasons, lecturers considered Pecha Kucha as a better mode of presentation compared to the traditional methods like Powerpoint. Implications of the study on teaching and learning were discussed